Analisis Situasi Luas Wilayah Reseptif Malaria di Kabupaten Gunungkidul Daerah Istimewa Yogyakarta Tahun 2021 - Atikah Mulyawati; Tri Wahyuni Sukesi; Surahma Asti Mulasari; Yohannes Didik Setiawan; Yeni Yuliani; Yuli Patmasari; Theresia Aprilia Girsang; Ita Latiana Damayanti (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
Gunungkidul Regency received an elimination certificate in April 2014, but in 2019 there was one imported case, and it is possible that indigenous transmission may have the potential to occur. Gunungkidul is also a tourist area visited by many domestic tourists who can come from malaria endemic areas. This study aims to map the malaria receptive area to determine early warning measure to maintain malaria elimination status. The research method is quantitative with observational descriptive. The data was obtained from the mapping of the malaria receptive area of the Yogyakarta BBTKLPP in 2021 in the form of larval survey results and the capture of nocturnal adult mosquitoes. The location of the activity is at two points, namely Ngawis Village, Karangmojo District and Pacarejo Village, Semanu District, Gunungkidul Regency. The results showed that Ngawis Village and Pacarejo Village were malaria receptive areas because Anopheles sp. larvae were found with a habitat index of 20.7% and 3.3%, which exceeded the quality standard of the Minister of Health RI No. 50 of 2017 and the capture of the Anopheles mosquito as a potential malaria vector in residential areas. The identified species are An. vagus, An. aconitus, and An. maculatus. Conclusion Ngawis Village has a higher malaria receptivity compared to Pacarejo Village, with more diverse breeding places and more adult mosquitoes caught. Both villages need to make efforts to reduce breeding places and implement an early warning system against malaria.